Nutritional composition and organoleptic quality of instant local black rice (cempo ireng) with moderate glycemic index - Dian Nurhayati Aprinia; Nirbaya Arindra; Permata Nusa Cassandra; Soekopitojo Soenar; Lukas Kurniawan Adi; Dwi Handoko Dody; Hapsari Anindya; Faza Sepbrina Aurelia; Oktavia Wahyuningsih Prastiwi Dwi; Ayu Puspitasari Diah; Athaya Nazhira; Yusuf Al Badwani Muhammad; et al. (BIO Web of Conferences)
This research aims to develop instant rice from local black rice variety, Cempo Ireng, that is safe for diabetes mellitus. Instant black rice was made through the process of soaking in sodium citrate, washing, cooking using a rice cooker, freezing in the freezer for 24 hours, thawing at room temperature, and drying using a dehydrator. There were 3 formula of instant black rice including (1) soaking in 5% sodium citrate at room temperature, (2) soaking in 5% sodium citrate at 500C, (3) soaking in 7% sodium citrate at 500C. All formulated instant black rice was then tested for its nutritional content (including anthocyanin, dietary fiber, amylose, amylopectin, starch, water content, ash, protein, fat, and carbohydrates). The black rice formula is also tested for hedonic quality by 35 semi-trained panelists. The formula 7% sodium citrate at 50°C has the highest score in color. The formula 7% sodium citrate at 50°C and 5% sodium citrate at room temperature have the same score for the rice aroma. The third formula was the best formula based on the panelists' choices and anthocyanin content. It was then tested for its glycemic index. The results showed that instant black rice has a moderate glycemic index of 60.